2010
DOI: 10.1002/anie.200906870
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Direct Arylation of Unactivated Arenes with Aryl Halides

Abstract: Iron tough: Various aryl halides were treated with unactivated arenes to form biaryl compounds in moderate to good yields. The reactions were carried out at relatively low temperature in the presence of a catalytic amount of FeCl3, with DMEDA as the ligand and LiHMDS as the base (see scheme; DMEDA=N,N'‐dimethylethane‐1,2‐diamine, HDMS=hexamethyldisilazanide).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…During the course of our studies on the iron-catalyzed coupling reaction of aryl halides with arenes, 8 we found that iron is not essential for the coupling to take place. After investigation of better conditions for the coupling in the absence of any transition metals, the system shown in Scheme 3 was found to be effective.…”
Section: ç Tert-butoxide-mediated Coupling With Arenesmentioning
confidence: 97%
“…During the course of our studies on the iron-catalyzed coupling reaction of aryl halides with arenes, 8 we found that iron is not essential for the coupling to take place. After investigation of better conditions for the coupling in the absence of any transition metals, the system shown in Scheme 3 was found to be effective.…”
Section: ç Tert-butoxide-mediated Coupling With Arenesmentioning
confidence: 97%
“…22 In the past few decades, direct arylation has developed into a promising synthetic method compared to traditional cross-coupling methods because it occurs with less synthetic steps, higher atom economy, and forms only environmentally benign byproducts. While a variety of transition metals have been discovered to promote these transformations (Scheme 1), 21,[24][25][26] including Pd, 22 Cu, [27][28][29][30][31][32][33][34] Ru, [35][36][37][38][39] Rh, [40][41][42][43] Ir, 44,45 Ni, [46][47][48][49] Co, [50][51][52] Fe, [53][54][55] Au, 56,57 literature reports in this field has been dominated by Pd-catalyzed direct arylation due to its high efficiency and broad scope. As a consequence, the recent 10 years have witnessed the intense development of Pd-catalyzed direct arylation as a powerful tool to prepare well-defined π-conjugated polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, C-H (bond) activation, cross-dehalogenative coupling, C-H (bond) functionalization, and catalytic direct arylation are generally employed. Although pioneering reports on the use of alternative metals for direct arylation have been published (Cu [25], Fe [26], Ni [27], Ir [28] or Co [29]), second-row transition metals in low oxidation states (Rh [30][31][32][33], Ru [34][35][36][37][38], and especially Pd [39][40][41][42][43]) are preferred as catalysts for these cross-dehalogenative couplings. The ligands required usually depend on the nature of the haloarene coupling partner.…”
Section: Introductionmentioning
confidence: 99%